2023
DOI: 10.1590/1413-785220233101e258453
|View full text |Cite
|
Sign up to set email alerts
|

S53p4 Bioactive Glass Putty in the Local Treatment of Cavitary Chronic Osteomyelitis

Abstract: Objective: Evaluating the clinical results of bioactive glass S53P4 putty for the treatment of cavitary chronic osteomyelitis. Methods: Retrospective observational study, including patients of any age with clinical and radiological diagnosis of chronic osteomyelitis, who underwent surgical debridement and implantation of bioactive glass S53P4 putty (BonAlive® Putty, Turku, Finland). Patients who underwent any plastic surgery on the soft tissues of the affected site or had segmental bone lesions or septic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…The alkaline microenvironment not only fosters osteogenesis by modulating immune regulation [ 51 ], but also impedes bacterial energy metabolism and kills bacteria ultimately [ 52 ]. Some studies have demonstrated that bioactive glass, such as S53P4, are safe and effective in treating of osteomyelitis and can control infections caused by multidrug-resistant S. aureus strains [ 53 ]. Upon implantation into patient's infectious bone defects, the bioactive glass product has demonstrated a high infection cure rate ranging from 70.3 % to 90 %, underscoring the reliable therapeutic effects of BSG in bone infection treatment [ [54] , [55] , [56] , [57] ].…”
Section: Discussionmentioning
confidence: 99%
“…The alkaline microenvironment not only fosters osteogenesis by modulating immune regulation [ 51 ], but also impedes bacterial energy metabolism and kills bacteria ultimately [ 52 ]. Some studies have demonstrated that bioactive glass, such as S53P4, are safe and effective in treating of osteomyelitis and can control infections caused by multidrug-resistant S. aureus strains [ 53 ]. Upon implantation into patient's infectious bone defects, the bioactive glass product has demonstrated a high infection cure rate ranging from 70.3 % to 90 %, underscoring the reliable therapeutic effects of BSG in bone infection treatment [ [54] , [55] , [56] , [57] ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the bioglass-based putty showed a greater eradication of the infection when compared with the bioglass in granules. In addition, the putty presentation facilitates intraoperative handling, especially when filling the bone cavity, with less possibility of heterotopic calcification and fistulisation of the product [25].…”
Section: Discussionmentioning
confidence: 99%